An estimate of the sediments volume entrainable by debris flow along strobel and south pezorìes channels at fiames (dolomites, italy) - Degetto, M.; Crucil, G.; Pimazzoni, A.; Masetto, C.; Gregoretti, C. (Italian journal of engineering geology and environment, 2011)
<span data-sheets-value="{"1":2,"2":"The area of Fiames is located on a narrow and flat valley, 2 km north to Cortina d’Ampezzo, and is bounded on the right side by the Pomagagnon and Pezorìes peaks. At the transition between rock vertical cliffs and talus, about twenty debris channels originate and affect the talus till the bottom of the valley. The Strobel and South Pezorìes channels were recently routed by debris flows in 2004 and 2006. Field surveys, topographical and geo-morphological measurements were carried out to recognize the sediments volume that the debris flow can entrain during triggering and routing phases. The estimate of the erodible sediment volume was obtained through the measurements of the geo-morphological and sediments features of source areas including their locations (channel bank or bottom). The resultant estimate can help in the design of the input debris flow hydrographs for dynamic modelling of debris flow and retain basins."}" data-sheets-userformat="{"2":13057,"3":{"1":0},"11":0,"12":0,"15":"Arial","16":10}">The area of Fiames is located on a narrow and flat valley, 2 km north to Cortina d’Ampezzo, and is bounded on the right side by the Pomagagnon and Pezorìes peaks. At the transition between rock vertical cliffs and talus, about twenty debris channels originate and affect the talus till the bottom of the valley. The Strobel and South Pezorìes channels were recently routed by debris flows in 2004 and 2006. Field surveys, topographical and geo-morphological measurements were carried out to recognize the sediments volume that the debris flow can entrain during triggering and routing phases. The estimate of the erodible sediment volume was obtained through the measurements of the geo-morphological and sediments features of source areas including their locations (channel bank or bottom). The resultant estimate can help in the design of the input debris flow hydrographs for dynamic modelling of debris flow and retain basins.